ANALISIS KEBUTUHAN UDARA PEMBAKARAN UNTUK MENGOPTIMALKAN PROSES PEMBAKARAN BOILER PT. PLN (PERSERO) SEKTOR PEMBANGKITAN ASAM ASAM UNIT 3 & UNIT 4 - Akhmad Syarief; Yudistira Bayu Setiambodo; Muhammad Nizar Ramadhan; A'yan Sabitah (Universitas Lambung Mangkurat, 2020)
The performance of a power plant unit is strongly influenced by various aspects, one of which is very determined by how the combustion process occurs in the combustion chamber, because it can affect the efficiency of the power plant itself, especially in the efficiency aspects of the boiler combustion process. To find out the efficient operation of the boiler, the operator as the holder of the power plant must understand what the combustion process is like in it. Good combustion will always require the right combination of fuel and air (oxygen). From the results of the research that has been done, it can be seen that if the actual amount of air flow needed for the combustion process is closer to the ideal air flow value it will indirectly increase the combustion efficiency value of the boiler.